Microbial Leaching of Uranium Ore - HAMIDIAN, H.; REZAI, B.; MILANI, S.A.; VAHABZADE, F.; SHAFAIE, S.Z. (Asian Journal of Chemistry, 2010)
The rapid growth demand for power follows that nuclear power industry has led to progressive exhaustion of high grade reserves of uranium ore and new extraction techniques should be developed to use along with low grade ore. On the other hand, the uranium recovery from low grade and refractory ores with conventional techniques of processing is very expensive and tough because these methods require high level of energy and capital costs. Therefore, making use of low cost and influential method is too significant for this issue. One proposed method is microbial leaching. Microbial leaching is regarded as one of the most promising and certainly the most revolutionary solution to these problems in comparison with pyrometallurgy or chemical metallurgy. Microbial leaching is the extraction of metals from their ores using microorganisms. Microbial technology offers an economic alternative to the mining industry. This paper intends to render a general overview of the microbial leaching research activities all over the world.